PHILOSOPHY IN MOTION: HARNESSING JAIPONG DANCE FOR SELF-CONFIDENCE DEVELOPMENT - Luthfiyyah Jihan Nasywa; Mudafiatun Isriyah; Weni Kurnia Rahmawati (EDUCATIONE, 2025)
This study addresses the persistent problem of adolescent self-doubt in school settings and the need for culturally responsive, evidence-informed interventions; in Indonesia, the values embedded in Jaipong dance offer a locally meaningful pathway to nurture confidence and courage. The objective was to design, validate, and pilot a counseling–learning module grounded in Jaipong philosophical values to reduce self-doubt among Grade-9 boarding students at SMP ADH DHUHA Jember. Using an R&D framework with the ADDIE model, we conducted needs analysis, blueprinting, iterative development, expert validation (content, language, design, practitioner usability; 5-point scale), and a small pre–post pilot with total sampling of the cohort. Data sources included observations, semi-structured interviews, student questionnaires (Likert 1–5), and expert rating sheets; analyses comprised percentage feasibility (Akbar–Sriwiyana thresholds), Aiken’s V/CVI for content validity, Cronbach’s alpha for reliability, paired t-tests/Wilcoxon (effect sizes), and thematic analysis with triangulation and member checking. Experts judged the module feasible to very feasible, reliability indices were acceptable, and validity indices met conventional cutoffs; the pilot suggested a downward trend in self-doubt and positive acceptability, while acknowledging small-sample limitations. We conclude that the module is context-appropriate, culturally resonant, and preliminarily effective, warranting a larger controlled evaluation. Practically, the study delivers a replicable procedure for schools to co-develop arts-informed counseling modules. Future work should expand sample size, include control groups, extend follow-up, and test mediators/moderators (e.g., confidence, courage, engagement).